Assessing the spatial knowledge gaps of Odonata diversity and conservation in the South American Pampa - Pires, Mateus; Martins, Fernanda; Palacio, Alejandro; Muzón, Javier; Vareira, Luisa; Juen, Leandro; Périco, Eduardo (Aquatic conservation, 2024)
Anthropogenic activities highly threaten neotropical freshwater habitats. Aquatic insects are sensitive to environmental alterations and thus considered under great risk due to such pressures. However, large‐scale gaps regarding the knowledge of the distribution of aquatic insect species remain in the Neotropics, particularly in the South American temperate grasslands (Pampas), hindering the knowledge of hotspots of aquatic insect diversity and the prioritization of conservation areas destined to protect their populations. Here, we review the current knowledge regarding the geographical distribution of Odonata species and use ecological niche models to estimate the areas with the highest potential richness of Odonata species in the Pampas. We also calculate a sampling effort index and interpolate it with maps of protected areas to identify the spatial knowledge gaps regarding their conservation in the region Our compilation of Odonata species records retrieved 237 species for the Pampa. However, Odonata species were recorded in less than 2% of the Pampa. Our findings indicated a higher potential diversity of Odonata in northeastern Argentina, southern Uruguay and southern Brazil. Interpolations of sampling effort index and protected areas showed that 95% of the area potentially rich in Odonata species fall outside protected areas. Our study highlights the shortfall regarding the knowledge of the distribution of Odonata diversity in non‐forest landscapes of the Neotropical region. It also shows that protected areas of the Pampa cover a minor area of the Odonata species range in the region.